2022
DOI: 10.1007/s00520-022-07264-3
|View full text |Cite
|
Sign up to set email alerts
|

Financial toxicity in female patients with breast cancer: a national cross-sectional study in China

Abstract: Purpose To quantify financial toxicity of female patients with breast cancer in China and investigate its factors and patients’ coping strategies. Methods The Comprehensive Score for Financial Toxicity (COST) is defined by using a structured questionnaire containing 12 items measuring perceived affordability of healthcare services, with the range of scoring of which being from 0 to 44 (higher score indicates lower financial toxicity). From January to March… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 48 publications
(89 reference statements)
3
17
0
Order By: Relevance
“…Moreover, the average out‐of‐pocket costs for our patients exceeded those of patients diagnosed with breast ($1823), colorectal ($1193), and lung cancer ($1649) 29 . In comparison to patients receiving cancer treatment, the HS population demonstrates FT levels similar to patients with breast, lung, and colorectal cancer 30–36 . While these comparisons do not deem HS a more burdensome disease or requiring more extensive health care coverage than any malignancy, they allude to the notion that the indirect costs of HS may be greater than what is perceived by the health care system.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Moreover, the average out‐of‐pocket costs for our patients exceeded those of patients diagnosed with breast ($1823), colorectal ($1193), and lung cancer ($1649) 29 . In comparison to patients receiving cancer treatment, the HS population demonstrates FT levels similar to patients with breast, lung, and colorectal cancer 30–36 . While these comparisons do not deem HS a more burdensome disease or requiring more extensive health care coverage than any malignancy, they allude to the notion that the indirect costs of HS may be greater than what is perceived by the health care system.…”
Section: Discussionmentioning
confidence: 87%
“…29 In comparison to patients receiving cancer treatment, the HS population demonstrates FT levels similar to patients with breast, lung, and colorectal cancer. [30][31][32][33][34][35][36]…”
Section: Insurance and Financial Factorsmentioning
confidence: 99%
“…[47][48][49] Four studies only reported the median of the costs which were not included in the data synthesis. [50][51][52][53] In addition, two studies only reported coping strategies 54,55 and two reported the proportion of catastrophic expenditure without reporting cost data. 56,57 According to the quality assessment for all included studies, 10 studies 26, [37][38][39][40][41]47,51,55,56 were assessed as high quality, 10 studies 27-29,36,42,43,46,52−54 at the middle level and 18 studies 21,23,24,[30][31][32][33][34][35]44,45,48,49,57 as low quality.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies investigated coping strategies when households with cancer patients shouldered expensive expenditures on cancer care (Table 5). 37,39,44,45,54,55 All studies reported borrowing money from relatives and friends or a loan. In two more recent studies, the reduction of household expenses (66.2%) or the reduction of expenses on basic health services (41.2%) were common strategies for addressing challenges caused by cancer care.…”
Section: Indirect Costsmentioning
confidence: 99%
See 1 more Smart Citation